(untitled) (Journal of human and social sciences, 2016)
This study explores the science of disagreement (Ilm al-Khilaf) and its rulings within Islamic jurisprudence, emphasizing the importance of understanding scholarly differences among jurists. Disagreement is natural and inevitable among learned scholars, past and present, and has continued throughout Islamic history. The research highlights that differences primarily concern practical legal rulings based on conjecture, which are subject to interpretation, rather than matters of fundamental religious principles. The study underscores that Islamic legislation derives from four main sources: the Qur’an, the Sunnah, consensus (Ijma’), and analogical reasoning (Qiyas). Scholars approach issues from various perspectives, leading to differences in wording, interpretation, and reasoning, which are considered a natural and divinely intended phenomenon. Disagreement, when pursued to seek truth, is a noble and essential science that integrates rules, principles, and ethics with broader Islamic knowledge and linguistic understanding. Reviving the jurisprudence of disagreement is vital for renewing Islamic jurisprudence and enhancing its role in contemporary social life. Such revival must be grounded in the objectives of Shariah, which prioritize public interest, justice, and mercy, while adhering to textual interpretations. Islamic jurisprudence includes fixed rulings derived from clear texts and flexible rulings based on conjectural texts, which allow for multiple interpretations. Differences among scholars, therefore, reflect sincere efforts to establish truth and justice, not personal desire or worldly gain. The research aims to elucidate the principles of disagreement, guide the handling of differing opinions, deepen enlightened understanding, and present the diverse methodologies of scholars. It also seeks to expand intellectual horizons by demonstrating the legitimacy of scholarly disagreement in Shariah, supported by Quranic texts, Prophetic traditions, and the views of jurists, showing that such differences occur naturally across all stages of Islamic legislation.